Time budget and habitat use of the Common Crane wintering in dehesas of southwestern Spain - Avilés, Jesus M. (Canadian Journal of Zoology, 2003)
In many bird species juvenile inexperience drastically reduces their survival, and parents must provide for them. I tested whether time budget and habitat use in adult wintering Common Cranes (Grus grus) in dehesas (pastoral woodland) of western Spain were affected by the presence of juveniles. Juvenile cranes devote less time to vigilance and spend more time feeding than adults in dehesas. Likewise, juveniles are involved in fewer aggressive encounters than adult cranes. Contrary to expectation, adults accompanied by juveniles devoted the same amount of time to vigilance and feeding and had the same intake rate than adults without juveniles in attendance. However, adult cranes with offspring in attendance were involved in more aggressive encounters than adults without juveniles in attendance when both adult groups were involved in large flocks. In contrast, when adults accompanied by juveniles were in small flocks they were involved in fewer aggressive encounters than adults without juveniles. I also detected a differential use of dehesas by adult cranes that was linked to juvenile presence and explained by the vulnerability of juvenile cranes in intraspecific social relationships. Adults with juveniles in attendance preferred dehesas with livestock where flock sizes were smaller than those in dehesas without livestock, and therefore where they might reduce the number of aggressive encounters with other cranes.
doi: 10.1139/z03-105doi: 10.1139/z03-105The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: Cranes; Dehesa; feeding (voyant); intake rate; livestock; parental investment; social structure